2010
DOI: 10.3139/146.110331
|View full text |Cite
|
Sign up to set email alerts
|

Deleterious phases resulting from the induction bending of thick-walled super-duplex pipework

Abstract: Deleterious phasesresulting from the induction bending of thick-walledsuper-duplexpipework Temperfree inductionbendingcanh aveasignificantimpacton the mechanicaland corrosion-resistanceproperties of thick-walled superduplexpipe. Sectionsfrom induction bentpipeweresolution annealed at1120 8 Cforv arious periodst osequentiallyeliminated ifferentdeleterious phases.Bycomparing the results of modified DL-EPR analysis,opticalm icroscopy,mechanicaland corrosion testingbeforeand aftert he various heatt reatments,itw a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…This is explained by the lower concentrations of austenite, which favors the segregation of nitrogen in the ferrite phase and the precipitation of Cr 2 N when cooling. Similar results were also found by [10][11][12]. The bent tubes (STB) showed a lower amount of chromium nitrides precisely for this reason, as can be seen comparing Figs.…”
Section: -Microstructural Characterizationsupporting
confidence: 86%
“…This is explained by the lower concentrations of austenite, which favors the segregation of nitrogen in the ferrite phase and the precipitation of Cr 2 N when cooling. Similar results were also found by [10][11][12]. The bent tubes (STB) showed a lower amount of chromium nitrides precisely for this reason, as can be seen comparing Figs.…”
Section: -Microstructural Characterizationsupporting
confidence: 86%
“…1. The form of chromium nitride which was present following induction bending was previously identified as Cr 2 N [3], which tends to form between 700 and 900 • C [5]. At the temperature at which induction bending is conducted the majority of the The results presented in this paper do not show that any of the surviving thermocouples stayed within any of the critical temperature ranges for prolonged periods of time.…”
Section: Discussionmentioning
confidence: 63%
“…The authors have previously suggested a thermal history based on the type and quantity of deleterious phases encountered in the bent samples [3]. However, having studied the thermocouple data, it appears that Cr 2 N most likely occurs during the immediate post-bend cooling of the pipe.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations